Omega-3 Fatty Acids as a Treatment for Pediatric Depression. A Phase III, 36 Weeks, Multi-Center, Double-Blind, Placebo-Controlled Randomized Superiority Study - Häberling, Isabelle; Berger, Gregor; Schmeck, Klaus; Held, Ulrike; Walitza, Susanne (Frontiers in Psychiatry, 2019)
Background: Depressive disorders in childhood and adolescence are a major health problem and often follow a chronic course with severe consequences in later life. Depressive disorders cause the highest burden of disease in this age group across all medical conditions. Treatment adherence is usually very poor and the use of antidepressant drugs is heavily debated, as suicidal ideations may increase, in particular in the early phase of treatment. Omega-3 fatty acids rich in eicosapentaenoic acid have shown some promising results in over a dozen small scale randomized controlled trials (RCTs) in adult major depressive disorders, with only very few published RCTs in children and adolescents. High quality phase III RCTs are missing. Methods and Design: The Omega-3-pMDD trial is a carefully designed phase III RCT to assess the efficacy and safety of omega-3 fatty acids in the early course of pediatric major depressive disorder (MDD). The study is designed as a multi-center, double-blinded, placebo-controlled, randomized clinical trial enrolling 220 patients aged 8 to 17 years meeting DSM-IV criteria for major depressive disorder of at least moderate symptom severity. After a single-blinded placebo-lead-in phase (7 to 10 days) patients are randomly assigned to omega-3 fatty acids or placebo over 36 weeks. Primary outcomes are changes in depression severity, as well as remission and recovery rates. Secondary outcome measures include the omega-3 index and inflammatory parameters as predictors of response. Data analysis will be performed in the intention-to-treat sample using a (generalized) linear random intercept regression model. Through sampling of blood, hair, saliva and urine further putative biological markers for depression and omega-3 fatty response will be investigated. Discussion: This trial addresses if omega-3 fatty acids play a role in the pathogenesis of pediatric MDDs and have antidepressant properties, in particular in clinically depressed children and adolescents with a pre-existing omega-3 fatty acid deficiency, increased markers of oxidative stress and/or markers of (low grade) inflammation. Ethics and Dissemination: The study was approved by the local ethics committees. The results will be published in peer-reviewed journals irrespective of specific outcomes. Trial registration: The study is registered with www.ClinicalTrials.gov protocol No NCT03167307.